Improved classifier chain methods based on heuristic optimization techniques for multi-label classification problem - Oyekunle, Adeleke Abdullahi (2022)
This thesis is about proposing multi-label classification (MLC) techniques for classification applications. In MLC, the task is to develop models that could predict multiple class labels